Sebuah Studi Evaluasi Non-Destruktif pada Las Keliling (Circumferential Weld) pada Shell Menara Turbin Angin Menggunakan Magnetic Particle Testing - Hery Tri Waloyo; Saeful Bahri (Kreator, 2026)
Welding is one of the most important processes in the fabrication of wind turbine tower structures, particularly in the circumferential weld joints of the shell section. The quality of the welded joint greatly determines the structural strength and operational reliability of wind turbines. This study aims to detect welding defects in circumferential weld joints of wind turbine tower shells using the Magnetic Particle Testing (MPT) method. The testing method employed is the wet visible type of MPT, which is a non-destructive testing technique used to identify surface and near-surface defects in ferromagnetic materials. The inspection process was conducted on a circumferential weld joint on a wind turbine tower shell. The inspection results revealed several indications of welding defects in the weld area, including cracks, porosity, and slag inclusions. The presence of these defects has the potential to reduce the quality and strength of the welded joint in the wind turbine tower structure. Therefore, corrective actions are required in the areas where defects were detected to ensure structural integrity and prevent potential component failure. This study demonstrates that Magnetic Particle Testing is an effective initial inspection technique for detecting defects in welded joints of wind turbine tower structures.